1995
DOI: 10.1111/j.1365-2125.1995.tb04458.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with simvastatin and pravastatin on cognitive function in patients with hypercholesterolaemia.

Abstract: The effects of equi-efficacious doses of the cholesterol-lowering drugs simvastatin (20 mg day-') and pravastatin (40 mg day-) on tests of cognitive function were investigated in a double-blind, placebo-controlled, 2-period (4 weeks per period), incomplete block, crossover study of 36 patients (24 per treatment) with hypercholesterolaemia. After 4 weeks neither of the active treatments differed significantly from placebo on any cognitive measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…This in turn suggests the possibility of premature cognitive decline by patients subjected to chronic stain treatment (Muldoon et al, 2004). In this regard, although prospective studies to date have failed to demonstrate a causal relationship between statin use and dementia (Wagstaff et al, 2003), the co-morbidities of hypercholesterolemic patients requiring chronic statin use might obscure such a relationship, while the time frames of these studies may have been too short for such an association to become manifest in any event (Cutler et al, 1995;Golomb et al, 2004). In this context, our results suggest the need for awareness of the possible toxicities accruing to long-term stain use, and identify one such potential toxicity, the premature differentiation and attendant long-term depletion of oligodendrocyte progenitor cells of the adult brain.…”
Section: Discussionmentioning
confidence: 89%
“…This in turn suggests the possibility of premature cognitive decline by patients subjected to chronic stain treatment (Muldoon et al, 2004). In this regard, although prospective studies to date have failed to demonstrate a causal relationship between statin use and dementia (Wagstaff et al, 2003), the co-morbidities of hypercholesterolemic patients requiring chronic statin use might obscure such a relationship, while the time frames of these studies may have been too short for such an association to become manifest in any event (Cutler et al, 1995;Golomb et al, 2004). In this context, our results suggest the need for awareness of the possible toxicities accruing to long-term stain use, and identify one such potential toxicity, the premature differentiation and attendant long-term depletion of oligodendrocyte progenitor cells of the adult brain.…”
Section: Discussionmentioning
confidence: 89%
“…[12][13][14][15] All had placebo rather than standard care comparators. RCTs (reported in 23 publications [13][14][15][36][37][38][39][40][41][42][43][44][45][46][47][48][50][51][52]55,56,62,64 ) enrolled subjects with normal cognition at baseline, four RCTs (reported in seven publications 12,54,[57][58][59][60][61] ) enrolled patients with AD, and three RCTs enrolled other cognitively impaired subjects (traumatic brain injury, 53,63 and neurofibromatosis type 1 49 ). Simvastatin (eight trials), pravastatin (eight trials), and lovastatin (six trials) were most frequently utilized in the statin RCTs.…”
Section: Assessment Of Heterogeneity and Meta-regression Analysesmentioning
confidence: 99%
“…In addition, although rare instances of statinassociated memory loss have been described (53), animal studies have indicated that the concentrations needed for memory impairment are generally much higher than the dose normally used in cholesterol-lowering therapy (31). Furthermore, various clinical trials have reported no significant effects of statins on cognitive performance (54)(55)(56)(57). Finally, it is worth noting that statins tend to increase serum plant sterol and stanol levels (58), which makes individuals on statin treatment an excellent population to study the effects of plant sterols and stanols.…”
Section: Discussionmentioning
confidence: 98%